Description and development of the tadpole of Rhacophorus feae (Anura; Rhacophoridae) - Kane, Daniel; Michaels, Christopher J; Tapley, Benjamin (Zootaxa, 2018)
The genus Rhacophorus Kuhl & Van Hasselt is currently known to contain 92 species of frogs (Frost 2018), distributed across south and south-east Asia. Rhacophorus feae Boulenger is a large member of this genus and has a seemingly expansive range been recorded from southern Yunnan in China, the Karen hills in Myanmar, northern Thailand, northern Laos and northern Vietnam (Chanard et al. 1999; Orlov et al. 2002; Nguyen et al. 2005; Stuart 2005; Yang 2008). It is currently included in the intrageneric R. dennysi group (Dubois 1986) along with R. duboisi Ohler, Marquis, Swan & Grosjean , R. dennysi Blanford, R. dugritei (David), R. minimus Rao, Wilkinson & Liu, R. hungfuensis Liu & Hu, R. dorsoviridis Bourret, R. nigropunctatus Liu, Hu & Yang, and R. smaragdinus (Blyth).